A novel amphiphilic oligopeptide induced the intrafibrillar mineralisation via interacting with collagen and minerals. Issue 11 (27th February 2020) - Wang, Qing-qing; Miao, Leiying; Zhang, He; Wang, Si Qing; Li, Quanli; Sun, Weibin
Abstract : The self-assembled oligopeptide inspired by CEMP1 achieved collagen mineralisation by binding with collagen and attracting calcium ions. Abstract : Mineralised collagen fibrils constitute the basic building blocks of bone, dentin and cementum. Noncollagenous proteins (NCPs) that are indispensable for collagen biomineralisation are not commercially available, and the mechanism of intrafibrillar mineralisation remains debatable. Herein, synthetic biomimetic molecules are regarded as alternative candidates for NCPs, and more convenient in revealing the mechanism of intrafibrillar mineralisation in vitro . Here, we fabricated a novel amphiphilic oligopeptide imitating a natural NCP. We aimed to investigate the effectiveness of the oligopeptide in intrafibrillar mineralisation and partially reveal the corresponding mechanism in vitro . The effectiveness of the oligopeptide in intrafibrillar mineralisation was characterised from the following aspects: (1) mineral interaction, (2) collagen binding and (3) induction of intrafibrillar mineralisation. Results indicated that the self-assembled oligopeptide could attract calcium ions inducing the formation of amorphous precursors; and bind onto the surface of collagen fibrils. These processes were mainly driven by the electrostatic attraction and hydrogen bonds. The self-assembled oligopeptide induced the intrafibrillar mineralisation of reconstituted collagen fibrils, in which the c -axis of apatite crystallites was roughly parallel to the long axis of the fibrils. The collagen mineralisation was achieved by binding with the self-assembled oligopeptide to increase the pool of mineralization precursors available for intrafibrillar mineralisation. In addition, the self-assembled oligopeptide induced dentin collagen remineralisation and formed a 30 μm-thick remineralised layer within 96 h. Our work sheds light on the fabrication of a novel biomimetic molecule for collagen mineralisation. The results should serve as a reference for understanding the mechanism of intrafibrillar mineralisation.